A skeptical appraisal of the bootstrap approach in fund performance evaluation. Issue 2 (14th April 2018) - Zhang, Huazhu; Yan, Cheng
Abstract: It has become standard practice in the fund performance evaluation literature to use the bootstrap approach to distinguish "skills" from "luck", while its reliability has not been subject to rigorous statistical analysis. This paper reviews and critiques the bootstrap schemes used in the literature, and provides a simulation analysis of the validity and reliability of the bootstrap approach by applying it to evaluating the performance of hypothetical funds under various assumptions. We argue that this approach can be misleading, regardless of using alpha estimates or their t‐statistics. While alternative bootstrap schemes can result in improvements, they are not foolproof either. The case can be worse if the benchmark model is misspecified. It is therefore only with caution that we can use the bootstrap approach to evaluate the performance of funds and we offer some suggestions for improving it.